2006
DOI: 10.1111/j.1440-1746.2006.04314.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of rabeprazole 10 mg and omeprazole 20 mg for the healing rapidity of peptic ulcer diseases

Abstract: Low-dose rabeprazole 10 mg has a similar efficacy for the healing rapidity of active peptic ulcer disease and symptom improvement compared with standard-dose omeprazole 20 mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
(71 reference statements)
0
15
0
1
Order By: Relevance
“…The typical rabeprazole dose is 20 mg; however, previous reports showed that 10 mg of rabeprazole was equivalent to 20 mg of omeprazole in gastric ulcer healing after 6 weeks [16]. The goal of our study was to compare the efficacy of 10 mg rabeprazole to 20 mg rabaprazole in patients with ESD-induced ulcers.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The typical rabeprazole dose is 20 mg; however, previous reports showed that 10 mg of rabeprazole was equivalent to 20 mg of omeprazole in gastric ulcer healing after 6 weeks [16]. The goal of our study was to compare the efficacy of 10 mg rabeprazole to 20 mg rabaprazole in patients with ESD-induced ulcers.…”
Section: Discussionmentioning
confidence: 95%
“…Among the many available PPIs, rabeprazole is commonly used in Asian countries because it is less affected by the CYP2C19 genetic polymorphism, which is more prevalent in Japan, China, and Korea than in western countries [15,16,24]. The typical rabeprazole dose is 20 mg; however, previous reports showed that 10 mg of rabeprazole was equivalent to 20 mg of omeprazole in gastric ulcer healing after 6 weeks [16].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Fort he managementof PU (induction of healing and maintenanceo fremission) bothsuppression of gastric acid secretion and eradication of Hpareimportantmainstays.Ing eneral,therei slittle overall differencei nPU healing ratesamong the PPIsand reported small differencescanbeexplained best bythe variable dosage regimensapplied [57,89,159].Eradication of Hpi saccomplished efficiently(80-90%e radication rates)by standardtriple therapywithaPPI, amoxicillin and clarithromycin ormetronidazole [17,29,91]and therewasno significantdifferenceamong the PPIs [35,36,76,141,151].…”
Section: Therapeuticuseo Fppis 51 Pepticulcermentioning
confidence: 99%
“…It should be noted that in contrast to H. pylori eradication, there is little overall difference in peptic ulcer healing rates among the PPIs in the management of PUD [195], and it is possible that pharmacogenomics may not explain interindividual differences enough to the extent that different dose regimens can be applied [4,197,198]. On a broader scale, a call for a pharmacogenetic-based dose alteration needs to be tempered with the global status of pharmacogenetic individualization of therapy, which remains in evolution and currently has limited application in medical practice [199].…”
Section: Expert Commentarymentioning
confidence: 99%